Seksualitas pada Remaja dan Dewasa Muda Laki-Laki dengan Autism Spectrum Disorder: Systematic Literatur Review - Toni Nugraha Jamaluddin HB; Haerani Nur; Dian Novita Siswanti (INSIGHT: Indonesian Journal Social Studies and Humanities, 2026)
Abstract. Sexuality in male adolescents with Autism Spectrum Disorder (ASD) is an important yet underexplored topic in educational and psychological literature. This study aims to synthesize empirical evidence regarding the profile of sexuality, factors influencing psychosexual development, and the effectiveness of sexuality education interventions among male adolescents and young adults with ASD aged 12–25 years. A Systematic Literature Review (SLR) guided by PRISMA 2020 was conducted through searches of PubMed, PsycINFO, ERIC, and Scopus databases using keywords related to ASD, sexuality, and male adolescents. Study quality was assessed using JBI Critical Appraisal Tools and synthesis was conducted through thematic synthesis. Of the 46 identified articles, 35 studies met the inclusion criteria after deduplication and screening. Results revealed three main findings: (1) male adolescents with ASD demonstrate comparable sexual interest to typically developing peers but more limited interpersonal sexual experience, alongside heightened vulnerability to sexual victimization; (2) social skills are the strongest predictor of positive psychosexual development, followed by parental involvement and cognitive factors; (3) Tackling Teenage Training (TTT) is the only program with Level I evidence (RCT) demonstrating significant improvement in psychosexual knowledge. It is concluded that evidence-based sexuality education initiated before puberty, characterized by concrete language, visual supports, repetition, and active parental involvement, constitutes an essential component of comprehensive ASD services.Keywords: Autism Spectrum Disorder, Male Adolescent Sexuality, Psychosexual Development, Sex Education